Lammy Review: will it change outcomes in the criminal justice system?. (January 2018) - Bridges, Lee
A forensic analysis from a criminal justice expert on the weaknesses in the findings and recommendations of the Lammy Review into Black, Asian and Minority Ethnic disproportionality in the UK's criminal justice system. It comments on the remit (which excludes policing), the lack of real action over police gang databases and the joint enterprise 'charge', the inadequate understanding of plea bargaining and influence of charging, the need for a deeper understanding of outcomes particularly at the Crown Court, and the weaknesses in merely asking for more Black, Asian and Minority Ethnic representation in the system. The statistical review, the author concludes, produces snapshots of marginal disproportionality at selected stages in the process and hence an episodic analysis of criminal justice, rather than looking at the overall system's effect in producing differential outcomes for the various ethnic groups. See also Liz Fekete, 'Lammy Review: Without racial justice, can there be trust?' ( Race & Class, doi: 10.1177/0306396817742074).